The truth about vitamins - Kendall, Dan; British Broadcasting Corporation ([United Kingdom] : BBC Active, 2006)
Explores research that counters vitamin advocate Linus Pauling's theories, suggesting that high doses of some vitamins may actually harm the human body. An alarming association with increased osteoporosis and cancer rates is one of several medical findings discussed
Title from title screen
Editor, Matthew Barrett ; graphic, Jason White ; sound, Lee Edwards, Ron Garson ; photography, Voughan Matthews, Dirk Nel, Tim Platten
Narrator: Ross Kemp
Keywords: Vitamins; Vitamins in human nutrition; Vitamins -- Synthesis; Vitamin tolerance